Analgesic Effects of Oxycodone in Combination With Risperidone or Ziprasidone: Results From a Pilot Randomized Controlled Trial in Healthy Volunteers - Nagpal, Ameet S.; Lodge, Daniel J.; Potter, Jennifer S.; Frazer, Alan; Tragus, Robin; Curtis, Megan E.; Boley, Angela M.; Eckmann, Maxim (Frontiers in Pain Research, 2022)
Background and Objectives Patients taking opioids are at risk of developing dependence and possibly abuse. Given the role of the mesolimbic dopamine system in opioid reward, blocking dopamine D2 receptors should limit the abuse liability of opioid analgesics. This pilot study evaluates the analgesic efficacy of oxycodone combined with an atypical antipsychotic (dopamine D2 receptor antagonist). Methods A randomized, double-blind, within-subjects, controlled trial in healthy volunteers was conducted at UT Health SA Pain Clinic. Fifteen volunteers with previous medical exposure to opioids were enrolled. Risperidone (2 mg) or ziprasidone (80 mg) in combination with oxycodone (5, 10, 15 mg) was administered. Pain intensity using the cold pressor test, Current Opioid Misuse Measure (COMM), Addiction Research Center Inventory (ARCI, opioid subscale), Drug likability with drug effects questionnaire (DEQ) were assessed. Results Oxycodone produced dose dependent increases in thermal analgesia on the cold pressor test that was significant at 10 and 15 mg (t = 3.087, P = 0.017). The combination did not significantly alter thermal analgesia. There was no significant effect of the combination on the ARCI or the POMS. Discussion and Conclusion The combination of an atypical antipsychotic with oxycodone does not alter analgesic response or increase the incidence of adverse effects when compared to oxycodone alone. Such information is critical for the development of drug combinations for the treatment of pain and provide the foundation for future studies of abuse potential in drug users. Scientific Significance This intervention in chronic pain patients is unique because it utilizes FDA approved drugs in combination to reduce abuse liability. The first step, and aim of this study, is to confirm the drug combination does not interfere with analgesic efficacy. The next step is to examine the combination in recreational drug users to assess the potential to block the euphoric effects of oxycodone. Ultimately, if this combination is effective, this approach could be beneficial in management of chronic pain.